2011
DOI: 10.3343/kjlm.2011.31.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in Growth Factor Concentrations in Platelet-rich Plasma and Its Influence on Human Mesenchymal Stem Cells

Abstract: BackgroundThe objective of this study was to explore whether individual variations in the concentration of growth factors (GFs) influence the biologic effects of platelet-rich plasma (PRP) on human mesenchymal stem cells (HMSCs).MethodsThe concentrations of 7 representative GFs in activated PRP (aPRP) were measured using ELISA. The effects of PRP on the proliferation and alkaline phosphatase (ALP) activity of HMSCs were examined using several concentrations of aPRP from 3 donors; the relationships between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 24 publications
6
67
1
1
Order By: Relevance
“…A number of studies have addressed the effect of PRP concentration on the proliferation of osteoblasts, periodontal cells, or mesenchymal stem cells [25][26][27][28][29]. Some authors have reported that PRP at higher concentrations failed to promote proliferation, and in some cases even suppressed it [14,30]. On the other hand, there are only a few studies on the effect of different concentrations of PRP on the proliferation of human chondrocytes [9,31,32] and synoviocytes [33].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have addressed the effect of PRP concentration on the proliferation of osteoblasts, periodontal cells, or mesenchymal stem cells [25][26][27][28][29]. Some authors have reported that PRP at higher concentrations failed to promote proliferation, and in some cases even suppressed it [14,30]. On the other hand, there are only a few studies on the effect of different concentrations of PRP on the proliferation of human chondrocytes [9,31,32] and synoviocytes [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, platelet lysates obtained by the other groups also contained high concentrations of TGF-b and PDGF in contrary to low levels of b-FGF or TNF-a. 15,[31][32][33] More importantly, TGF-b as the major constituent of HPR plays a key role in early osteogenic differentiation, but is not potent per se to induce terminal osteogenic differentiation as well. [34][35][36] Therefore, osteogenic inducer-independent action of HPR on differentiation of BMSCs toward an osteogenic lineage, as we showed here, implies that osteogenic potential of HPR may due in part, but not restricted to the distinct presence of TGF-b.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sex differences have been reported in the literature which add an additional variable to consider when harvesting PRP from older patients. For example, higher concentrations of these growth factors were found in female subjects [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is currently recognized as an effective treatment for diabetic wounds [10], surgical wounds [9], and musculoskeletal injuries [11]. There have been reports of generally positive patient outcomes with a very low occurrence rate of adverse events, and while there have not been a large number of randomized clinical trials performed for some of the desired applications, such as ligament and tendon repair [12], the application of PRP for other conditions such as osteoarthritis has definitively yielded better results than alternatives such as hyaluronic acid [13] and corticosteroids [14].…”
Section: Platelet-rich Plasmamentioning
confidence: 99%